Keterikatan Karyawan pada Perusahaan PT XYZ - Paramarta, Dionisius Sunu Adinugraha; Saragih, Eva Hotnaidah (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
The role of human resources in the company is very important because it is the main driver for achieving company goals. The ability and willingness possessed by employees is the biggest contribution to a company. The company is expected to be able to manage the workforce in the company appropriately, so that they have an attachment to the company and make an optimal contribution to achieving the company's goals and excellence. This research was conducted to determine the level of employee engagement at XYZ company with descriptive quantitative research methods through online surveys using the UWES (Utrecht Work Engagement Scale) questionnaire version 17 questions. From the results of processing 35 data collected, it was found that the overall level of employee engagement at PT XYZ had a score of 4.14 out of 6.00 (in the Average category). Recommendations are focused on improving the engagement aspect which has low scores in almost all demographic categories, namely the vigor dimension for statement No. 3 "When I wake up in the morning, I feel like going to work (VI03)". The contents of the recommendation are to provide breakfast facilities, pick-up employees, or reward role models who are enthusiastic when leaving for work in the morning by assessing the punctuality of their arrival. In addition, to retain employees who have entered the high category, it is recommended to provide entertainment facilities during break hours, for example sofas, massage chairs, and others.